2019
DOI: 10.4236/as.2019.106059
|View full text |Cite
|
Sign up to set email alerts
|

Applying Rhizobacteria on Maize Cultivation in Northern Benin: Effect on Growth and Yield

Abstract: The aim of the study was to investigate the effects of five plant growth-promoting rhizobacteria (PGPR) (Bacillus panthothenicus; Pseudomonas Cichorii; Pseudomonas Putida; Pseudomonas syringae and Serratia marcescens) on the growth and yield of maize on a ferruginous soil under field condition. Maize seeds were inoculated with 10 ml of bacterial suspension. Study was conducted in a completely randomized design with fifteen treatments and three replicates. A half-dose of recommended (13, 17, 17 kg•ha −1) NPK wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 47 publications
(40 reference statements)
4
12
1
Order By: Relevance
“…On the central and northern sites, the best maize plant crown diameters were obtained with P. putida + ½ dose of NPK and Urea, which exceeded farming practice by 18.08%. These results are close to the 25.24% obtained by [21] on maize plants treated with P. putida + ½ dose of NPK and Urea on ferruginous soil in Northern Benin. Similar results (26.12% increase) on maize plant height were reported by [33] with the inoculation of the rhizobacteria (Cn1) among the six (06) isolated from rhizospheric soils of two plants Convolvulus arvensis and Polygonum plebeium in Parkistan.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…On the central and northern sites, the best maize plant crown diameters were obtained with P. putida + ½ dose of NPK and Urea, which exceeded farming practice by 18.08%. These results are close to the 25.24% obtained by [21] on maize plants treated with P. putida + ½ dose of NPK and Urea on ferruginous soil in Northern Benin. Similar results (26.12% increase) on maize plant height were reported by [33] with the inoculation of the rhizobacteria (Cn1) among the six (06) isolated from rhizospheric soils of two plants Convolvulus arvensis and Polygonum plebeium in Parkistan.…”
Section: Discussionsupporting
confidence: 87%
“…In Northern Benin (Ouénou), the best height of maize plants was obtained with the full dose of NPK and Urea (T3) followed by P. putida + ½ dose of NPK and Urea (T2) with respective increases of 25.05% and 23.15% compared to the Farmers' Practice (T1). These results are close to the 35, 24% recorded by [21] on maize plants treated with P. putida + ½ dose of NPK and Urea on ferruginous soil in Northern Benin. This recorded difference was related to the fertility gradients of the environments where the trials were carried out.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The role of PGPRs in resolving several constraints such as soil degradation, water stress, and declining soil fertility that limit agricultural production has been widely proven [15]. The use of plant growth-promoting bacteria (PGPR) can be a promising alternative that can reduce the application of chemicals and improve crop yields and plant health [16] [17] [18]. For example, [19] has shown that PGPRs can increase nutrient bioavailability in the rhizosphere.…”
Section: Introductionmentioning
confidence: 99%